POTENSI AGENSIA HAYATI DAN NABATI DALAM MENGENDALIKAN PENYAKIT BUSUK RIMPANG JAHE - Loekas Soesanto, Sudarmono, Nur Prihatiningsih, Abdul Manan, Endang Iriani, dan Joko Pramono (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2005)
Potency of biological and botanical agents in controlling ginger rhizome rot. Research aimed at knowing integrity of various control agents in controlling causal agent of ginger rhizome rot. The research was carried out at Gowak Village, Pringsurat District, Temanggung Regency, Central Java Province, from November up to May 2004. Randomized Block Design was used with treatments of biological (Bacillus sp. with density of x ï‚´ 1010 cfu ml-1 suspension and Trichoderma harzianum 20 g crop-1), of botanical (clove leaves powder of 20 g crop-1 and neem seeds extract of 25 ml crop-1), and synthetical agents (benomil with concentration of 2 g l-1) either alone or in combination, with three replicates. Variables observed were incubation period, disease intensity, infection rate, number of leaves per crop, crop height, and ginger production per hectare. Result of the research showed that the location was endemic of the disease. The treatments could generally retard the incubation period and the infection rate, decrease the disease intensity, and increase the ginger production. The highest ginger yield was obtained from the plot given Trichoderma harzianum (Trikonis), either alone or in combination with the dry clove leaves of 10 g crop-1 as many as four times with interval of seven days started from seedling planted.